Knowledge of Breast Cancer Screening and Protection Among Female Health Care Professionals of Federal Government Polyclinic Hospital, Islamabad, and its Allied Dispensaries : Knowledge of Breast Cancer Screening Among Female Health Care Professionals - Shan, Saima; Ehsan, Jovaria; Jabeen, Farkhanda; Baseer, Maliha; Hameed, Aisha; Rehman, Asim; Zarmeena, .; Rehana, . (Pakistan Journal of Health Sciences, 2025)
Breast cancer is one of the leading causes of mortality among women globally, and Pakistan has the highest breast cancer prevalence in Asia. Despite the importance of early detection through screening and awareness, data on healthcare professionals’ (HCPs) knowledge and practices in Pakistan are limited. Objectives: To evaluate the knowledge of breast cancer screening and protection among female HCPs at the Federal Government Polyclinic Hospital, Islamabad, and its allied dispensaries. Additionally, it sought to identify gaps in awareness and guide future interventions. Methods: A cross-sectional, descriptive study was conducted over six months at the Federal Government Polyclinic Hospital, Islamabad, and its allied dispensaries. A structured, self-administered questionnaire was distributed to 530 female HCPs, including physiotherapists, psychologists, administrative officers, doctors, nurses, and support staff. Data were analyzed using SPSS version 25.0. Results: The majority of participants were nurses (37.7%) and aged between 21 and 25 years (24.5%). A large proportion reported no family history of breast cancer (92.8%) and were non-smokers (89.8%). Knowledge regarding breast cancer symptoms, risk factors, and screening methods varied across different roles and educational levels, with junior doctors and postgraduates showing the highest knowledge levels. Despite this, gaps were identified in understanding protective measures and screening practices. Conclusions: While awareness of symptoms and risk factors was adequate, there were notable deficiencies in knowledge regarding protective practices and screening behavior. These gaps highlight the need for targeted educational interventions among female HCPs.